Heavy metals in soil and vegetables grown with municipal wastewater in Lahore - Hamid, A; Mushtaq, A; Nazir, R; Asghar, S (Bangladesh Journal of Scientific and Industrial Research, 2017)
Heavy metals contamination of fruits and vegetables as a consequence of wastewater irrigation is most important concern today. Present study measures heavy metals concentration (Cr, Cu and Pb) in soil and vegetable samples collected from agriculture area around four major drains of Lahore (Hudiara drain, BabuSabu drain, Chota Ravi drain and Kharak drain). Results show that concentration of Cu, Cr and Pb in soil samples were in compliance with WHO and EU standards, with an average of 2.221 ± 1.184, 5.314 ± 1.0511 and 3.864 ± 1.6095 mg/kg respectively. Cu content in vegetables ranged from 0.4-18.9 mg/Kg (average of 4.11 ± 6.639 mg/kg), was within limits while Cr in Lady Finger, from Chota Ravi drain area, was 13.2 mg/Kg which is higher than permissible limit (2.4 mg/Kg). While Pb concentration in vegetables samples varied between 0.7 -8.1 mg/Kg (Mean 2.329 ± 2.592 mg/kg), which was also higher than the standard (0.3 mg/Kg). Bangladesh J. Sci. Ind. Res. 52(4), 331-336, 2017